Super-resolution ultrasonic Lamb wave imaging based on sign coherence factor and total focusing method. (1st May 2023) - Zhu, Wenfa; Xiang, Yanxun; Zhang, Haiyan; Zhang, Mengke; Fan, Guopeng; Zhang, Hui
Abstract: Improving the resolution of ultrasound array imaging systems for multiple defects in a measured medium is a popular research topic in nondestructive testing technology. However, because of the diffraction of acoustic waves, the resolution of ultrasound array imaging systems must follow Rayleigh's criterion and hence is limited, and defects with a spacing smaller than the resolution limit cannot be identified using conventional ultrasound imaging methods. Ultrasonic Lamb waves have dispersion and mode conversion characteristics, and the scattering acoustic field after the interaction between Lamb waves and defects is usually complex, making it even more difficult to improve the imaging resolution. In this paper, ultrasonic Lamb wave imaging is investigated with the sign coherence factor-total focusing method (SCF-TFM) when the spacing of the detected defects is smaller than the resolution limit, and the imaging resolution limit of SCF-TFM is analyzed. Experiments on a single blind-hole defect show that the lateral resolution of the SCF-TFM imaging is nearly twice as high as that of the total focusing method (TFM), with a higher signal-to-noise ratio. For experiments on multiple blind-hole defects, the resolution of the SCF-TFM improves by 71.32%, which is higher than that of the TFM when the spacing of the detected defects is larger than the resolution limit. The SCF-TFM enables super-resolution imaging and achieves a higher resolution limit than time-domain topological energy when the spacing of the detected defects is smaller than the resolution limit.